Seven-tesla magnetic resonance imaging of the nervus terminalis, olfactory tracts, and olfactory bulbs in COVID-19 patients with anosmia and hypogeusia - Kirsch, Claudia F. E.; Khurram, Syed Ali; Lambert, Daniel; Belani, Puneet; Pawha, Puneet S.; Alipour, Akbar; Rashid, Shams; Herb, Mackenzie T.; Saju, Sera; Zhu, Yijuan; Delman, Bradley N.; Lin, Hung-Mo; et al. (Frontiers in Radiology, 2024)
Linking the olfactory epithelium to the central nervous system are cranial nerve one, the olfactory nerve and cranial nerve "0" the nervus terminalis (NT). Since there is minimal expression of the virus entry protein, angiotensin-converting enzyme 2 (ACE2), in cranial nerve one, olfactory bulbs (OB), and olfactory tracts (OT), it is unclear how SARS-CoV-2 causes anosmia (loss of smell) and hypogeusia (reduction of taste). The NT are often overlooked nerve fibers found in all vertebrates, including humans adjacent to the OB and OT. In animal models, NT express ACE-2 receptors, suggestive of a possible SARS-CoV-2 viral entry site in humans. The purpose of this study was to determine whether ultra-high field 7 Tesla (7T) magnetic resonance imaging (MRI) could visualize the NT, OB, and OT in healthy controls and COVID patients with and without anosmia or hypogeusia and qualitatively assess for OB, OT volume loss and T2 alterations in the NT, OB and OT. In this study, 7T MRI visualized the NT in all imaged subjects. In addition, the increased occurrence of T2 hyperintensity in the NT, OB, and OT in COVID patients with anosmia or hypogeusia was statistically significant when compared to healthy controls and when compared to COVID patients without anosmia or hypogeusia. We propose that viral infection of the NT may reduce blood supply to olfactory pathways and thereby may cause anosmia.